010 Association between Objective Sleep Duration and DNA methylation in Adolescents. (3rd May 2021) - Larsen, Michael; He, Fan; Imamura, Yuka; Berg, Arthur; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward; Gehrman, Philip; Fernandez-Mendoza, Julio
Abstract: Introduction: Insufficient sleep and circadian misalignment are highly prevalent in adolescents and have been associated with physical and mental health disorders. Several genome wide association studies (GWAS) in adults have identified genes that may be involved in the regulation of sleep and circadian traits. However, little is known regarding the epigenetic basis and significance of short sleep duration in adolescence, a critical developmental period. Methods: To investigate the association between objective sleep duration, as measured by 9-hour in-lab polysomnography (PSG), and DNA methylation in GWAS-informed sleep-related genes, data from 263 adolescents of the Penn State Child Cohort (12-23y, 55.9% male, 23.2% racial/ethnic minorities) were analyzed. Using DNA extracted from peripheral leukocytes, epigenome-wide and GWAS-informed single nucleotide resolution of DNA methylation in cytosine-phosphate-guanine (CpG) sites and surrounding regions were obtained. Multivariable-adjusted linear regression models assessed the association between PSG sleep duration and site-specific methylation levels. Covariates in these models included sex, age, race/ethnicity, body mass index percentile, and psychoactive medication use (i.e., stimulants, anti-depressants, anxiolytics, sedatives, and/or anti-psychotics). P-values were adjusted using the Benjamini & Hochberg method to correct for false discovery rate and, thus, q-values are reported. Results: PSG sleep duration was associated with differential methylation at 162 intragenic sites in the epigenome-wide analysis with a q<0.05. In GWAS-informed analysis, five genes were associated with altered DNA methylation, by which shorter PSG sleep duration was associated with hypermethylation in MAD1L1 (q=0.02), MAP2K1 (q=0.03), and RBM19 (q=0.01) and with hypomethylation in Brain Enriched Guanylate Kinase Associated (BEGAIN; q=0.0005) and SLC39A8 (q=0.02). Conclusion: Objective sleep duration in adolescents is associated with altered DNA methylation in genes previously identified in adult GWAS of sleep and circadian traits. Importantly, our data also provides evidence for a potential epigenetic link between objective short sleep duration and genes involved in postsynaptic density (BEGAIN), circadian regulation (MAP2K1/RBM19) as well as internalizing (MAD1L1) and psychotic (SLC38A8) disorders. Support (if any): NIH Awards Number R01HL136587, R01MH118308, R01HL97165, R01HL63772, UL1TR000127